MULTI FAKTOR KUALITAS WEBSITE - Anwariningsih, Sri Huning (JURNAL GAUNG INFORMATIKA, 2011)
Internet technology is significant growth in the software industry. The existence of millions of web address as one sign of the development of internet technology. Until now, the Internet is still believed to be one of the media to disseminate information. Internet more trusted by developers and users to obtain the desired information without looking at the resources. Most of the web developers pay less attention to the quality of the web. There are some developers who tend to take attention to the look and less concerned with the content and vice versa. In fact a lot of factors that must be considered when a developer will design and develop the web. A website should be consider software quality and also meet the quality factors of the design and the content. There are several methods used in assessing software quality factors, among which are Mc Call and ISO 9126. While the methods used to measure the quality of the website and the WebQual include methods Waller.This paper aims to review what are the quality factors that must be considered by a website designer to design a good website based on software quality and website quality.